Examen especial al componente cartera de crédito vencida de la cooperativa de ahorro y crédito Riobamba ltda. de la ciudad de Riobamba agencia matriz. periodo 2016 - Llerena Lucio, Lorena Alexandra (2018)
In this research an analysis has been made about the delinquency of the loan portfolio of the Savings and Credit Cooperative Riobamba Ltda. In which objectives were set in order to determine inconsistencies, internal and external factors that affect the recovery of the portfolio, in the state of the art we can find the background of the investigation as well as the theoretical foundation that served us during the same. Regarding the methodology, our type of research was exploratory and descriptive, we had a very large population so we proceeded to apply the sample, and for the collection of information we used techniques such as observation, survey and interview. In addition, audit techniques and procedures were applied to obtain sufficient, competent evidence that allowed us to verify compliance with credit policies. For this, we rely on the information and documentation provided by the Cooperative's officers. This special examination was developed according to the following stages: planning: where the programs were established and the objectives were established; finally, the environment of the Cooperative's information system was known; execution: in this phase the sampling technique, surveys and all the planned procedures were developed, that is to say, the analysis of the main items of the financial statements and the findings were identified and finally we made the communication of results where the to know the main findings with their respective conclusions and recommendations that have been reached with the present investigation